1999
DOI: 10.1037/0022-0167.46.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Measuring attitudes regarding bisexuality in lesbian, gay male, and heterosexual populations.

Abstract: Who fills out a "lesbian" questionnaire? The interrelationship of sexual orientation, years out, disclosure of sexual orientation, sexual experience with women, and participation in the lesbian community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
404
5
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(429 citation statements)
references
References 33 publications
(47 reference statements)
19
404
5
1
Order By: Relevance
“…Research on lesbian families is of interest in its own right, and it is important to include studies on lesbian women in mainstream research (Herek, Kimmel, Amaro, & Melton, 1991;More & Rochlen, 1999). However, research in the field of planned lesbian families may also lead to a better understanding of family processes and of the development of children in 'normal' families as well.…”
Section: Discussionmentioning
confidence: 99%
“…Research on lesbian families is of interest in its own right, and it is important to include studies on lesbian women in mainstream research (Herek, Kimmel, Amaro, & Melton, 1991;More & Rochlen, 1999). However, research in the field of planned lesbian families may also lead to a better understanding of family processes and of the development of children in 'normal' families as well.…”
Section: Discussionmentioning
confidence: 99%
“…Their results were best summarized in two categories: tolerance of bisexuality, and the (dis)belief in the stability of bisexuality as an identity and the (dis)belief in the stability of bisexual people as romantic partners and friends. Mohr and Rochlen (1999) found that while both heterosexual and homosexual samples scored across almost the entire range (1-5) on both their tolerance of and their belief in the stability of bisexuality, both samples' mean scores were above the mid-point.…”
Section: Attitudes Towards Bisexuals and Bi-negativitymentioning
confidence: 99%
“…For example, Mohr and Rochlen (1999) conducted a study to measure the attitudes towards bisexuality in both heterosexual and homosexual populations. Their results were best summarized in two categories: tolerance of bisexuality, and the (dis)belief in the stability of bisexuality as an identity and the (dis)belief in the stability of bisexual people as romantic partners and friends.…”
Section: Attitudes Towards Bisexuals and Bi-negativitymentioning
confidence: 99%
“…Because participants could not select gay or lesbian as separate identities (i.e., the option in the survey was gay/lesbian/ homosexual), these identities could not be separated further. Bisexual and pansexual people were combined because both identities involve attraction to multiple genders, so the groups may experience similar marginalization from heterosexual people and the gay and lesbian community (Mohr & Rochlen, 1999). Covariates were entered first including gender identity, age, and highest level of education.…”
Section: Resultsmentioning
confidence: 99%